Antibodies against Glucan, Chitin, and Saccharomyces cerevisiae Mannan as New Biomarkers of Candida albicans Infection That Complement Tests Based on C. albicans Mannan - Sendid, B. (American Society for Microbiology (ASM), 2008)
Antibodies against Saccharomyces cerevisiae mannan (ASCA) and antibodies against synthetic disaccharide fragments of glucans (ALCA) and chitin (ACCA) are biomarkers of Crohn's disease (CD). We previously showed that Candida albicans infection generates ASCA. Here, we explored ALCA and ACCA as possible biomarkers of invasive C. albicans infection (ICI). ASCA, ALCA, ACCA, and Candida mannan antigen and antibody detection tests were performed on 69 sera obtained sequentially from 18 patients with ICIs proven by blood culture, 59 sera from CD patients, 47 sera from hospitalized subjects colonized by Candida species (CZ), and 131 sera from healthy controls (HC). ASCA, ALCA, and ACCA levels in CD and ICI patients were significantly different from those in CZ and HC subjects (P < 0.0001). In ICI patients, these levels increased as infection developed. Using ASCA, ALCA, ACCA, and Platelia Candida tests, 100% of ICIs were detected, with the kinetics of the antibody response depending on the patient during the time course of infection. A large number of sera presented with more than three positive tests. This is the first evidence that the detection of antibodies against chitin and glucans has diagnostic value in fungal infections and that these tests can complement more specific tests. Future trials are necessary to assess the value of these tests in multiparametric analysis, as well as their pathophysiological relevance.